Intestinal Anti-tissue Transglutaminase2 Autoantibodies: Pathogenic and Clinical Implications for Celiac Disease - Maglio, Mariantonia; Troncone, Riccardo (Frontiers in Nutrition, 2020)
Celiac disease (CD) is a systemic disease that primarily affects the small intestine. The presence of anti-tissue transglutaminase 2 (anti-TG2) antibodies in the serum, as well as the presence of autoimmune phenomena, account for the inclusion of CD among autoimmune diseases. Anti-TG2 autoantibodies are produced at intestinal level, where they could be deposited even before they appear in circulation. The mechanisms are still not completely defined, but a central role seems to be played by gliadin-specific T cells. Interestingly limited somatic mutations have been observed, another important aspect being the biased use of a heavy chain encoded by the VH5 gene. Conflicting data have been produced over the years on the effect of anti-TG2 antibodies on TG2 function. Although the presence of anti-TG2 antibodies in serum is considered a hallmark of CD and relevant from a clinical viewpoint, the role of these autoantibodies in the development of the celiac lesion remains to be defined. In the years different technical approaches have been developed to detect and measure intestinal CD-associated autoantibody production. Two aspects can make intestinal anti-TG2 antibodies relevant from a clinical viewpoint: the first is their suggested ability in potential coeliac patients to predict evolution towards a full blown enteropathy; the second is their possible role in revealing a condition of reactivity to gluten in patients with absence of CD-associated autoantibodies in their serum. In fact, the detection of specific CD autoantibodies production in the intestine, in the absence of serum positivity for the same antibodies, could be not specific for CD and merely attributable to intestinal inflammation; alternatively, it could be suggestive of a very early condition of gluten reactivity. In conclusion, the role of mucosal anti-TG2 antibodies in pathogenesis of CD is unknown. Their presence, the modalities of their production, their gluten dependence render them a unique model to study autoimmunity.